Optimization of flotation assay conditions for syndapin binding to phosphatidic acid containing liposomes - Piaścik, Magda; Zegarlińska, Jolanta; Sikorski, Aleksander F.; Czogalla, Aleksander (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2017)
Flotation is one of the best method for preliminary identification of protein-lipid interactions. In most widely used approach it utilizes large unilamellar vesicles, that are excellent models of freestanding membranes and do not require any additional components, like solid supports or beads that are needed in other methods commonly used for protein-lipid binding studies. Here we present results obtained during our studies on phosphatidic acid - syndapin interactions and discuss some technical aspects of this method underlying how relatively small changes in the conditions can influence the results.